Analisis Pengaruh Lokasi Strategis dan Kecepatan Pengiriman Terhadap Kepuasan Konsumen pada CV. Maju Muliya Farm - Raflin Raflin; Muhajirin Muhajirin; Rosa Yuliati; Siti Asyitah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of strategic location and delivery speed on customer satisfaction at CV. Maju Muliya Farm. The research employed a quantitative approach with a causal associative research design. The study population consisted of all customers of CV. Maju Muliya Farm in Pajo District, Dompu Regency, with a sample of 100 respondents selected using purposive sampling. Data were collected through a questionnaire using a five-point Likert scale and analyzed using IBM SPSS Statistics version 26, including validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, coefficient of determination, t-test, and F-test. The results indicate that strategic location has a positive and significant effect on customer satisfaction, with a t-value of 9.597 and a significance value of 0.000. Delivery speed also has a positive and significant effect on customer satisfaction, with a t-value of 4.157 and a significance value of 0.000. Simultaneously, strategic location and delivery speed have a significant effect on customer satisfaction, as indicated by an F-value of 57.228 and a significance value of 0.000. The coefficient of determination (R²) of 0.541 indicates that the two independent variables explain 54.1% of the variation in customer satisfaction, while the remaining 45.9% is influenced by other factors not examined in this study. Strategic location was found to be the most dominant variable affecting customer satisfaction.